2012
DOI: 10.1002/art.33444
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical injury suppresses autophagy regulators and pharmacologic activation of autophagy results in chondroprotection

Abstract: Objective Mechanical injury induces cell death in cartilage and triggers a remodeling process that ultimately can manifest as osteoarthritis (OA). Autophagy is a process for turnover of intracellular organelles and macromolecules that protects cells during stress responses. This study determined changes and functions of autophagy following mechanical injury to cartilage. Methods Bovine and human cartilage explants were subjected to mechanical impact (40% strain, 500 ms). Cell viability, sulfated glycosaminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 51 publications
8
113
0
Order By: Relevance
“…Mechanistic target of rapamycin complex 1 (mTORC1) intracellular signalling pathway is an autophagic regulator that when inhibited activates the process of autophagy [31]. Inhibition of mTORC1 was reported to protect against surgery-induced OA in mice [26,32]. Taken together, these findings confirmed the role of autophagy in the development of OA.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Mechanistic target of rapamycin complex 1 (mTORC1) intracellular signalling pathway is an autophagic regulator that when inhibited activates the process of autophagy [31]. Inhibition of mTORC1 was reported to protect against surgery-induced OA in mice [26,32]. Taken together, these findings confirmed the role of autophagy in the development of OA.…”
Section: Discussionsupporting
confidence: 74%
“…Aging is an important risk factor for the development of OA and is associated with the progressive accumulation of damaged macromolecules and organelles in somatic cells [27], potentially mediated by downregulation of the autophagic disposal of such damaged cellular components [28]. Autophagy-related proteins unc-51-like autophagy activating kinase 1 (ULK1), Beclin1 and microtubule-associated protein 1A/1B-light chain 3 (LC3) are reported to be expressed at high levels in healthy human cartilage [25,29,30], however, their expression decreases during OA [25,26]. Mechanistic target of rapamycin complex 1 (mTORC1) intracellular signalling pathway is an autophagic regulator that when inhibited activates the process of autophagy [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Activation of autophagy prevents the damage of articular cartilage resulting from aging, surgically induced osteoarthritis, as well as mechanical injury and glucocorticoid stimulation. [24][25][26][27] Settembre et al have found that loss of SUMF1 (sulfatase modifying factor 1), an enzyme-activating sulfatase, impairs autophagy and leads to dwarfism characterized by severely shortened skeletal elements. 28 Inactivation of CTGF/ CCN2 (connective tissue growth factor) in mice leads to severe chondrodysplasia resulting from increased stress-induced death and decreased autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy, which is in part related to the reduced expression of autophagic regulators, is compromised in osteoarthritic cartilage. In articular cartilage, autophagy does not only occur in response to mechanical injury, but is also deficient with aging (8,27). Autophagy is characterized by the formation of autophagosomes and their fusion with lysosomes.…”
Section: Discussionmentioning
confidence: 99%